Pattern magic 2 - Nakamichi, Tomoko, ....- (London : King, 2011)
More Pattern Magic is the cult pattern-cutting text from Japan, partner to the original Pattern Magic book. Inspiring and exciting, this volume takes a creative approach to pattern cutting, with more step-by-step projects for fashion designers and dressmakers to enjoy. This book looks at creating interesting surfaces, optical illusions and curved shapes through pattern cutting. All the basic information you need to start pattern cutting is included, from the basic block to measurements and scaling. Each project is beautifully illustrated with clear diagrams and photographs showing the stages of construction, the muslins (toiles) and the finished garments. these easy-to-follow illustrations and detailed instructions make it easy to create stunning, sculptural clothes.
Keywords: Patroonsnijden ; Japan